OP0085 Safety of long-term (UP TO 6 YEARS) canakinumab therapy (<2, 2−<4 and 4−<8mg/kg) in patients aged <4 to 65 years from beta-confident registry. (12th June 2018) - Kuemmerle-Deschner, J.B.; Walker, U.A.; Tilson, H.H.; Hawkins, P.N.; van der Poll, T.; Franke, K.; Speziale, A.; Vritzali, E.; Hoffman, H.H.
Abstract : Background: The β-confident registry (NCT01213641 ), a multicenter, long-term (6 years; yrs), prospective, observational study has demonstrated the safety and effectiveness of canakinumab (CAN) in real life CAPS patients (pts) according to their phenotypes. 1 Here we report long-term safety of CAN in pts with CAPS and other autoinflammatory syndromes, enrolled in the β-confident registry, according to their age and dose administered. Objectives: To monitor the long-term safety of different CAN doses (<2, 2−<4 and 4−<8 mg/kg) across different age groups (<4 to 65 years) in pts with CAPS and other autoinflammatory syndromes. Methods: Cumulative safety data were reported as exposure adjusted incidence rate per 100 pt-years (IR/pyr) from the enrollment of the first pt (November 2009) until end of study (December 2015). Pts were followed up for at least 1 year. The protocol did not mandate any visits or procedures. All observed and reported AEs and SAEs were recorded for the following age groups:<4-, 4−<12-, 12−<18-, 18−<65 and≥65 years. Results: Of the 285 pts enrolled, 21% (n=60) discontinued the study mainly due to loss of follow-up (35%, n=21) followed by AEs (10%, n=6), poor efficacy (8%, n=5) and pt preference (3%, n=2). In total, 1114 AEs and 155 SAEs were reported in 223 pts (110.7 IR/100 pyr) and 83 pts (15.4 IR/100 pyr), respectively. Exposure adjusted incidence rate of AEs (IR/100 pyr) among pts in the <4 and 4 -<12 year age group, were lowest in the pts who received <2 mg/kg dose (130.3 and 59.7, respectively) compared to pts who received 2 -<4 mg/kg (450.8 and 169.6, respectively) and 4 -<8 mg/kg (121.5 and 90.0, respectively) CAN dose. In pts aged 12 -<18 years, IR/100 pyr were lowest in pts who received 2-<4 mg/kg dose (118.2) compared to pts who received <2 mg/kg (169.6) and 4 -<8 mg/kg (139.4) CAN dose. Similarly, in the 18 -<65 year age group, IR/100 pyr were lowest in pts who received <2 mg/kg dose (93.1) compared to pts who received 2-<4 mg/kg (100.7) and 4 -<8 mg/kg (154.4) CAN dose. In the ≥65 year age group, IR/100 pyr decreased with increase in dose (<2 mg/kg: 26, 2−<4 mg/kg: 17). Overall, 5, 13, 19, 84 and 7 SAEs were reported in <4-, 4−<12-, 12−<8-, 18−<65 and≥65 year age groups, respectively. One death (metastatic rectal adenocarcinoma in a 76-yr-old MWS patient) was reported. Conclusions: The β-confident registry is the largest CAPS cohort documented in a registry. In general, incidence of adverse events in each dose group increased with age (<4−<65 years). However, no meaningful pattern of AEs was observed with increased dose for each age group. Long-term treatment with canakinumab demonstrated favourable safety profile which was similar to that reported earlier 2 and is well tolerated in CAPS patients aged <4 to 65 years. Reference: [1] Kuemmerle-Deschner JB, et al. Ann Rheum Dis2015;74(S2):850. [2] Hoffman HM, et al. Arthritis Rheumatol 2016;68(suppl 10). Acknowledgements: The study was sponsored by Novartis Pharma AG Disclosure of Interest: J. Kuemmerle-Deschner Consultant for: Novartis Pharmaceutical Corporation, SOBI, and Baxalta, U. A. Walker Consultant for: Novartis Pharmaceutical Corporation, H. Tilson Consultant for: Novartis Pharmaceutical Corporation, P. N. Hawkins: None declared, T. van der Poll: None declared, K. Franke Consultant for: Novartis, A. Speziale Employee of: Novartis, E. Vritzali Employee of: Novartis, H. Hoffman Grant/research support from: Burroughs-Wellcome, Consultant for: Novartis Pharmaceutical Corporation, Sobi, Speakers bureau: Novartis Pharmaceutical Corporation